Penyuluhan dan Pemeriksaan Kadar Asam Urat (dalam Darah) pada Masyarakat Desa Bangga Kec. Dolo Selatan, Kab. Sigi, Prov Sulawesi Tengah - Hermin Lastri Gintoe; Andi Lindhemuthianingrum; Astri Febriana Iffaf (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
This activity aims to increase public knowledge about gout and conduct uric acid level checks in Bangga Village, Dolo Selatan District, Sigi Regency, Central Sulawesi Province. The main problem faced is the high incidence of gout, which is often caused by unhealthy eating patterns and lack of knowledge about gout. The methods used include interactive counseling and uric acid level checks with the Point of Care Testing (POCT) tool, carried out on January 8, 2024. Of the 15 participants who took part in the activity, 9 people were found to have high uric acid levels and 6 people with normal levels. The results showed that most of the respondents who had high uric acid levels came from the older age group. This activity succeeded in increasing public awareness of the importance of a healthy diet and is expected to encourage behavioral changes in maintaining health.